1995
DOI: 10.1111/j.1651-2227.1995.tb13684.x
|View full text |Cite
|
Sign up to set email alerts
|

Healthy eating for infants–mothers’attitudes

Abstract: Mothers' perceptions of desirable nutritional practices in infant feeding were examined using a questionnaire consisting of open and closed questions. A total of 1004 mother-infant pairs were recruited from a mixture of urban and rural areas in England. The sample represented a cross-section of socioeconomic groups and educational backgrounds. Mothers' attitudes to healthy eating for infants revealed some misconceptions; 83% felt that a high fibre intake was important or very important and 87% that a low fat i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
16
0

Year Published

1999
1999
2015
2015

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 3 publications
1
16
0
Order By: Relevance
“…A recent study of 55 children in the US found that 22% of children at 12 months and 33% of children at 18 months consumed less than 30% of energy from fat (Picciano et al, 2000). Furthermore, a British study has shown that it is not well understood that the dietary recommendations for children are different from those for adults -in this study most mothers believed a low-fat diet to be desirable even for infants (Morgan et al, 1995). Unfortunately, there is very little information on the relationship between fat intake and dietary quality in representative free-living populations of children under 2 y of age (Räsanen & Ylönen, 1992;Lagström et al, 1999).…”
Section: Introductionmentioning
confidence: 67%
“…A recent study of 55 children in the US found that 22% of children at 12 months and 33% of children at 18 months consumed less than 30% of energy from fat (Picciano et al, 2000). Furthermore, a British study has shown that it is not well understood that the dietary recommendations for children are different from those for adults -in this study most mothers believed a low-fat diet to be desirable even for infants (Morgan et al, 1995). Unfortunately, there is very little information on the relationship between fat intake and dietary quality in representative free-living populations of children under 2 y of age (Räsanen & Ylönen, 1992;Lagström et al, 1999).…”
Section: Introductionmentioning
confidence: 67%
“…It is possible that these guidelines may confuse mothers, affecting the choice of milk they provide for their child. It is not well understood by the public that the recommendations on fat intake for adults and children differ -in one study of mothers' attitudes they were shown to perceive a low-fat diet to be desirable even for infants (Morgan et al, 1995). Watt et al (2000), in a reanalysis of the NDNS data, looked at drink consumption in 1675 British children aged 1.5 -4.5 and found that 32% were having semi-skimmed and 4% skimmed milk.…”
Section: Discussionmentioning
confidence: 99%
“…In a previous study, Morgan et al 8 explored views of women in the UK about infant feeding and they were troubled by the fact that over 80% of women considered a high fibre intake and a low fat intake important. In our study, most women held views consistent with the 1995 Guidelines 4 in relation to fat-reduced milk, which is not recommended for infants or toddlers.…”
Section: Discussionmentioning
confidence: 99%
“…Information on parents' interpretations of the basis for nutritional recommendations, or rationales for alternative practices, has rarely been sought 8 . Furthermore, there is little information about the extent of concerns which parents may have that are not a focus of guidelines and dietary surveys.…”
mentioning
confidence: 99%